Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.molliq.2016.09.101
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 2,2,2-trifluoroethanol on water studied by using third derivatives of Gibbs energy, G

Abstract: We determined the excess partial molar enthalpy and the excess partial molar volume, HTFE E , VTFE E , of 2,2,2-trifluoroethanol (TFE) in TFE-H2O at 25.0 ˚C. We then evaluate the TFE-TFE interactions in terms of enthalpy and volume, HTFE-TFE E and VTFE-TFE E , graphically without resorting to any model dependent fitting functions. Both model-free third derivatives indicate that TFE is a hydrophobic solute and that as other hydrophobic alkyl mono-ols there are three distinct mixing schemes, Mixing Scheme I, II,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…57 In fact, our previous calorimetric analysis found that the Mixing Scheme I of TFE-H2O is at xTFE < 0.04. 55 Correspondingly, as shown in Figure 8, a33 likely took the value larger than 1 at the TFE mole fractions < ~0.03 (< ~1.5 M), implying that there was a possibility so that Δ 𝛤 /g became lower than Δ𝛤 /g obtained from the ideal homogeneous model of 𝑎 gg (𝑎 gg = 1). It can be said that the precise KBIs data obtained from the scattering method enable us to observe the specific and complex behavior.…”
Section: Two Different Regimes In the Excess Preferential Binding Mec...mentioning
confidence: 89%
See 1 more Smart Citation
“…57 In fact, our previous calorimetric analysis found that the Mixing Scheme I of TFE-H2O is at xTFE < 0.04. 55 Correspondingly, as shown in Figure 8, a33 likely took the value larger than 1 at the TFE mole fractions < ~0.03 (< ~1.5 M), implying that there was a possibility so that Δ 𝛤 /g became lower than Δ𝛤 /g obtained from the ideal homogeneous model of 𝑎 gg (𝑎 gg = 1). It can be said that the precise KBIs data obtained from the scattering method enable us to observe the specific and complex behavior.…”
Section: Two Different Regimes In the Excess Preferential Binding Mec...mentioning
confidence: 89%
“…This tendency has also been reported in the data of concentration fluctuation. 36 We note that, by 1propanol (1P)-probing methodology, TFE is more hydrophobic than 1P and is hydrophobic nearly similar to TBA; 55,57 the 1Pprobing methodology determines the hydrophobicity of a solute in its aqueous solutions in dilute region, defined as Mixing Scheme I, where the solute does not form aggregation structure with each other and parameters such as the hydration number of water molecules around the solute are evaluated. 57 On the other hand, in the previous SAXS study, the hydrophobicity is characterized as the low-concentration shift of the maximum of I(0)/V.…”
Section: Zero-angle Scattering Intensitymentioning
confidence: 99%
“…That TFE can denature the secondary structure at a lower volume fraction clearly establishes it as a stronger denaturing agent than t BuOH. TFE and t BuOH have comparable hydrophobicities, 61 but the former is a stronger hydrogen-bonding donor, owing to a higher acidity of its −OH group. The results validate our contention that hydrogen bonding is primarily responsible for the stability of the secondary aggregate and the emergence of supramolecular chirality in self-assembled D-PhePBI.…”
Section: ■ Introductionmentioning
confidence: 99%